Obtaining the membership function by using the neural network in Istanbul stock exchange to find the relation between the low and closing prices - Karanfil, Salih (Pro Mathematica, 2001)
By using neural network, the relationship between the low price and the closing price in IMKB is developed by a fuzzy membership function.